Effect of Prestroke Glycemic Variability Estimated Glycated Albumin on Stroke Severity and Infarct Volume in Diabetic Patients Presenting With Acute Ischemic Stroke - Lee, Sang-Hwa; Jang, Min Uk; Kim, Yerim; Park, So Young; Kim, Chulho; Kim, Yeo Jin; Sohn, Jong-Hee (Frontiers in Endocrinology, 2020)
Background: We investigated whether prestroke glycemic variability, represented by glycated albumin (GA), affects the initial stroke severity and infarct volume in diabetic patients presenting with acute ischemic stroke. Methods: We evaluated a total of 296 acute ischemic stroke patients with diabetes mellitus who were hospitalized within 48 hours of stroke onset. GA was measured in all acute ischemic stroke patients consecutively during the study period. The primary outcome was the initial National Institute Health Stroke Scale (NIHSS) score. The secondary outcome was infarct volume on diffusion-weighted imaging, which was performed within 24 hours of stroke onset. Higher GA (≥16.0%) was determined to reflect glycemic fluctuation prior to ischemic stroke. Results: The number of patients with higher GA was 217 (73.3%). The prevalence of a severe initial NIHSS score (>14) was higher in patients with higher GA than in those with lower GA (3.8% vs 15.7%, p=0.01). The proportion of participants in the highest quartile of infarct volume was higher in the higher GA group (11.4% vs 36.4%, p<0.001). A multivariable analysis showed that higher GA was significantly associated with a severe NIHSS score (odds ratio, [95% confidence interval], 7.99 [1.75-36.45]) and large infarct volume (3.76 [1.05-13.45]). Conclusions: Prestroke glucose variability estimated by GA was associated with an increased risk of severe initial stroke severity and large infarct volume in acute ischemic stroke patients with diabetes mellitus.